Galactagogues and Lactation: Considerations for Counseling Breastfeeding Mothers. Issue 3 (May 2022) - Balkam, Jane J.
Abstract: Development of a milk supply is a complex process that is not always understood by women who are breastfeeding. Galactagogues are substances commonly used by breastfeeding women who perceive that they have an insufficient milk supply. They can be herbal substances or pharmaceuticals. Herbal galactagogues are advertised and sold to women as capsules, cookies, milk shakes, and teas, as well as other forms of herbal supplements. Herbal galactagogues are classified as dietary supplements and not reviewed or regulated by the U.S. Food and Drug Administration. There are limited data on their safety and efficacy. Women experiencing problems with their milk supply should receive a thorough and thoughtful assessment of the situation. There are many factors that should be considered when counseling breastfeeding women about use of galactagogues. The physiology of lactation, process of milk supply development, and the evidence for use of galactagogues are reviewed to add to the knowledge of nurses and other health care providers working with women who are breastfeeding. Abstract : Galactagogues are sometimes used by new mothers who are breastfeeding to enhance their milk supply. However, there is minimal evidence that these products are safe or efficacious. Since they are considered dietary supplements, they are not reviewed or regulated by the U.S. Food and Drug Administration. In this article, the evidence and lack thereof for galactagogues to increase breast milk supply are reviewed. Nurses can use this information to help breastfeeding mothers make an informed decision about galactagogues and temper their expectations of these products in successfully solving a milk supply issue.